Pendampingan Budidaya Tanaman Hortikultura dengan Metode Pertanian Organik di Pondok Pesantren Banyulana - Nawangsari, Yuli; Zaidan Rahmat Nurhayat; M. Ghiffari Farrel N.; M. Shofwan Sahal S.; Hilmi Saepul Anwar; Ilham Nidza Mulhaq; Moh. Ilzar Firmansyah; Agus Candra Winata; Dehan Rafi E.P; Rizqi Zulfa F.A.; Ahmad Dzaki A.F.; Rafli Rayyis Hakim; Agan Muhammad Zein (ACITYA BHAKTI, 2025)
Banyulana Islamic Boarding School has approximately 1 hectare of land with the potential to support food self-sufficiency through horticulture. This community service activity aimed to improve the ability to cultivate organic horticulture and to strengthen the pesantren’s internal food supply. The method used was a participatory-mentoring approach (introduction, preparation of planting media, planting, maintenance, and harvesting), carried out for about one month with the participation of n = 11 students and n = 20 santri. Evaluation was conducted through field observations, documentation, and participant feedback (interviews/discussions). The results included the implementation of caisim, kale, shallot, and melon cultivation; the application of cultivation processes according to organic guidelines; and qualitative reports of increased participant understanding. Limitations of the program were the short duration and the absence of quantitative pre–post measurement.